Green School Curriculum and Curricular Practices Quest for Sustainable Development - Namdeo, R. Pushpa (JOURNAL OF INDIAN EDUCATION, 2020)
Education is one of the most important tools for the progress of the nation. Environmental education has always been a priority area in curriculum development programmes. Environmental education is not just about learning. It is about understanding the environmental issues confronting our planet and changing our behaviours as well. Developments in science and technology have not only made human living more comfortable but created several problems to ecological balance and to the environment. Hence, environmental education should equip children to transform scientific knowledge into optimum utilisation without affecting the environment. This could be achieved when inter and intra disciplinary approaches are practiced. Progress and development have become synonymous with the introduction of new technologies and products, aimed at making life better, safer and more viable. But, there have been instances where apparently useful products and technologies have turned out to be capable of inflicting extremely detritus impact on environment and development in the long run. Realising the importance of preparing younger generations to protect environment and maintain ecological balance for sustainable development, school curriculum from time to time emphasises the need for promoting environmental awareness to develop environment friendly behaviour. Keeping this rationale as the base, the researcher conducted the research on awareness about green school curriculum and curricular practices for sustainable development among elementary school teachers. The sample of 50 elementary school teachers from Wardha were selected using random sampling method for this study. The collected data were subjected to qualitative analysis.